Los códigos de buen gobierno corporativo en las entidades sin ánimo de lucro: en especial en las fundaciones (Codes of good corporate governance in non-profit organizations: especially in foundations) - Belén García Álvarez (Oñati Socio-Legal Series)
Non-Profit Organizations must deal too with corporate governance problems. Therefore, it can be convenient that these types of Organizations have Codes of Good Corporate Governance in order to achieve an optimum attainment of their purposes of general interest and a higher responsibility and efficiency in the administration of the organization. This necessity makes clear especially in Organizations with partnership public-private. In a Code of Good Corporate Governance must deal several aspects, as transparency, accountability, duties and rights of donors and beneficiaries of the foundation, duties fiduciaries of the board members and directors, and enforcement (including options of private enforcement).